2007
DOI: 10.1002/gj.1075
|View full text |Cite
|
Sign up to set email alerts
|

Diversification patterns of Early and Mid Ordovician graptolites in South China

Abstract: During the Early and Mid Ordovician, graptoloids underwent a dramatic diversification. Many clades (e.g. anisograptids, dichograptids and biserials) originated and subsequently diversified during this interval, playing the most important roles in the evolution history of graptolites. In this study we conduct an analysis of the generic and species diversity history of Early to Mid Ordovician graptolites from the Yangtze Region (platform) and Jiangnan Region (slope) of South China, and provide evidence that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This is shown in microfossil assemblages from this region, such as chitinozoans (Liang and Tang, 2016), acritarchs (Yan et al, 2011), conodonts (Wu et al, 2012). Interestingly, the diversity of graptolites was high but more diversified in the Jiangnan region (Zhang et al, 2007). During late Fl1 to early Fl2, sea-level rose and the rimmed shelf changed to mixed sedimentation ramp along with sufficient supply of terrigenous materials (Luan et al, 2017).…”
Section: Co-evolution Between Paleo-environments and Biodiversitymentioning
confidence: 95%
See 1 more Smart Citation
“…This is shown in microfossil assemblages from this region, such as chitinozoans (Liang and Tang, 2016), acritarchs (Yan et al, 2011), conodonts (Wu et al, 2012). Interestingly, the diversity of graptolites was high but more diversified in the Jiangnan region (Zhang et al, 2007). During late Fl1 to early Fl2, sea-level rose and the rimmed shelf changed to mixed sedimentation ramp along with sufficient supply of terrigenous materials (Luan et al, 2017).…”
Section: Co-evolution Between Paleo-environments and Biodiversitymentioning
confidence: 95%
“…Spatiotemporally diachronous radiations in clades and data biases characterize the GOBE and continuously hinder our understandings (Servais and Harper, 2018;Harper et al, 2021;Servais et al, 2021Servais et al, , 2023. As a potential cradle for radiation (Harper et al, 2013;Stigall et al, 2019), the GOBE in South China was well-developed during the Early-Middle Ordovician (Zhan et al, 2010;Deng et al, 2021), as shown by the early biodiversification of several clades during this interval (Zhan et al, 2005;Zhang et al, 2007;Liang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The species’ highest occurrence there is in the Acrograptus filiformis graptolite Biozone of the Yangtze Platform (Liang et al . 2018), which correlates with a level in the middle Floian, either in the upper part of Stage Slice Fl1 (Zhang et al 2007, 2010; Wang et al . 2013) or in Fl2 (Zhang et al .…”
Section: Chitinozoan Assemblages From South Walesmentioning
confidence: 97%
“…Dapingian) and lower Darriwilian Stage, and as ranging from the Azygograptus suecicus graptolite Biozone to the Undulograptus austrodentatus graptolite Biozone. As the suecicus Biozone spans the Floian-Dapingian boundary in South China (Zhang et al 2007(Zhang et al , 2010, it follows that the lowest occurrence of Bursachitina laminaris there is likely to be close to the base of the Dapingian Stage (Fig. 7).…”
mentioning
confidence: 99%
“…In addition, all confirmed Early Floian graptolite records previously mentioned from the Northwest of Argentina (Toro and Brussa, 2003;Albanesi et al, 2008;Brussa et al, 2008) have been incorporated (presence-absence matrix available upon request to the authors). A comparison was made with those faunal associations recently reviewed from equivalent stratigraphic levels of Baltoscandia (Egenhoff and Maletz, 2007), Great Britain (Zalasiewicz et al, 2009), North America (Jackson and Lenz, 2006;Williams and Stevens, 1988) and Southwest China (Zhang et al, 2007).…”
Section: Paleoecological and Paleobiogeographical Analysismentioning
confidence: 99%